1999
DOI: 10.1177/001440299906500302
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Early Childhood Programs in Inclusive and Noninclusive Settings

Abstract: This study assessed factors that contributed to global program quality in early childhood settings. The sample consisted of 180 community-based child care centers from 12 geographically and economically diverse regions in North Carolina. The Early Childhood Environment Rating Scale (ECERS) total mean score was usedas theprimary measure ofglobal program quality. The studyfound that 62 (34%) ofthe early childhoodprograms reported enrolling at leastone child with disabilities. The study also found that inclusive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 19 publications
5
53
1
3
Order By: Relevance
“…Many researchers have found that higher levels of preparation correlate positively with better quality child care services (Burchinal, Howes, & Kontos, 2002;Kontos et al, 1995 andLove et al, 1996;Whitebook, Howes, & Phillips, 1990) and more positive outcomes for children enrolled in child care centers (Burchinal, Lee, & Ramey, 1989;Burchinal et al, 2000;Cost, Quality and Child Outcomes Study Team, 1995;Howes, Phillips, & Whitebook, 1992Phillips, McCartney, & Scarr, 1987, as well as in child care homes (Clarke-Stewart, Vandell, Burchinal, O'Brien, & McCartney, 2002). The same associations between caregiver preparation and child care quality hold true for inclusive preschool settings, where ratings of global quality have been found to be substantially higher in child care classrooms where teachers have bachelor's degrees or child care credentials (Buysse et al, 1999). Yet education and training levels remain low, and few states require a bachelor's degree for providers.…”
Section: Workforce and Quality Issues Affecting Inclusionmentioning
confidence: 77%
See 2 more Smart Citations
“…Many researchers have found that higher levels of preparation correlate positively with better quality child care services (Burchinal, Howes, & Kontos, 2002;Kontos et al, 1995 andLove et al, 1996;Whitebook, Howes, & Phillips, 1990) and more positive outcomes for children enrolled in child care centers (Burchinal, Lee, & Ramey, 1989;Burchinal et al, 2000;Cost, Quality and Child Outcomes Study Team, 1995;Howes, Phillips, & Whitebook, 1992Phillips, McCartney, & Scarr, 1987, as well as in child care homes (Clarke-Stewart, Vandell, Burchinal, O'Brien, & McCartney, 2002). The same associations between caregiver preparation and child care quality hold true for inclusive preschool settings, where ratings of global quality have been found to be substantially higher in child care classrooms where teachers have bachelor's degrees or child care credentials (Buysse et al, 1999). Yet education and training levels remain low, and few states require a bachelor's degree for providers.…”
Section: Workforce and Quality Issues Affecting Inclusionmentioning
confidence: 77%
“…The troubling overall quality of American child care increases the challenge of ensuring that children with disabilities experience the excellent interventions and classroom supports they need. Nonetheless, two studies suggest that the overall quality in inclusive preschool settings may be somewhat better than that observed in segregated settings (Buysse et al, 1999;La Paro, Sexton, & Snyder, 1998), though in neither study was a representative sample of child care settings examined or comparisons made of inclusive versus non-inclusive child care in centers or family child care homes.…”
Section: Workforce and Quality Issues Affecting Inclusionmentioning
confidence: 97%
See 1 more Smart Citation
“…The ECERS-R is one of the most widely used observational instruments to measure the general quality of early childhood programs serving children between the ages of 2 and 6 years (Buysse, Wesley, Bryant, & Gardner, 1999;Mathers, Linskey, Seddon, & Sylva, 2007). Revised in 1998, the newest version of ECERS-R includes additional indicators to measure program quality in inclusive settings (Harms, Clifford, & Cryer, 2005).…”
Section: Instrumentsmentioning
confidence: 99%
“…The ECERS-R has been used in many national large-scale studies to measure program quality (Burchinal, Howes, & Kontos, 2002;Buysse et al, 1999;Early et al, 2006;Lambert, Abbott-Shim, & McCarty, 2002;La Paro, Sexton, & Snyder, 1998;Phillips, Mekos, Scarr, McCartney, & Abbott-Shim, 2000) and effectiveness of professional development (Campbell & Milbourne, 2005;Fukkink & Lont, 2007;Mathers et al, 2007). Many countries like Canada, England, Finland, Hungary, Greece, and Germany are using this instrument widely for purposes of research and program improvement.…”
Section: Instrumentsmentioning
confidence: 99%